Marked Dominance of methicillin Resistant Staphylococcus aureus among Iraqi Patients - Heba K. Tawfeeq; Muthanna Hamid; Harith Jabbar Fahad Al-Mathkhury (Indian Journal of Forensic Medicine & Toxicology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) infection in human beings and animals stands out asone of the leading pathogens causing nosocomial and community infections. Likewise, slightly increasingdrug resistance in MRSA has narrowed the treatment choices. This work focuses on estimating the prevalenceof MRSA in Baghdad, Iraq. A total of 130 specimens were collected from patients visiting various hospitalsin Baghdad, Iraq. The present results revealed that 50 (92.6%) isolates were identified as Staphylococcusaureus. Noticeably, mecA gene was detected in 44 (88%) isolates. Hence, the light must be shed on thismarked prevalence of methicillin resistant S. aureus.